Analisis Kinerja Perusahaan CV. Bali Indah dengan Metode Balanced Scorecard - PS. Saraswati; DP. Darmawan; K Suamba (JURNAL MANAJEMEN AGRIBISNIS, 2017)
ABSTRACTANALYSIS OF COMPANY PERFORMANCE OF CV. BALI INDAHWITH BALANCED SCORECARD METHODBusiness competition has raised the work standard in various dimensions suchas quality, cost, and smooth operation. The challenge caused by the increasingcompetition is that companies or institutions will do anything that is consideredimportant for strategic competitiveness and overall business improvement. That is,companies will always compete to attract customers by offering various facilities atcompetitive prices. This situation will obviously encourage the management to makecertain strategies in order to win the competition and achieve companies ultimategoals. This study entitled "Analysis of Company Performance of CV. Bali Indah withBalanced Scorecard method. The company's performance is looked from fourperspectives of Balanced Scorecard namely financial perspective, customer, internalbusiness processes, learning and growth. The aim of this study is to analyze theperformance of CV. Bali Indah based on the four perspectives of the BalancedScorecard.The Performance of CV. Bali Indah from a financial perspective in this studywere assessed using Liquidity Ratio (current ratio and quick ratio), ProfitabilityRatio (net profit margin, return on assets and return on equity), Solvency Ratio (totalasset to debt ratio and networth to debt ratio), Leverage ratio (total debt total assetsratio and total debt to equity ratio) and Activity Ratio (total assets turn over). Theperformance of costumer perspective used the customer acquisition and customersatisfaction index. Internal business process performance was assessed by usingManufacturing Cycle Effectiveness (MCE). The performance assessment of learningand growth perspective was done by assessing the capability of employees bymeasuring employee productivity and employee satisfaction index. Based on the study findings, it can be concluded that CV. Bali Indah fromFinancial Perspective of the year 2011-2014 is rated good. From the customerperspective, customer acquisition fluctuated and customer satisfaction index resultsarevery good (customers were satisfied with their transactions with CV. Bali Indah).Assessment on internal business process perspective by assessing product ordertransaction using Cycle Manufacturing Effectiveness is rated good. Product ordertransaction has run effectively.In term of learning and growth perspective, employeeproductivity fluctuated from 2011-2014 and the employee satisfaction index result isgood (employees are satisfied with their employment in CV. Bali Indah)Key Words: Balanced Scorecard, Financial Perspective, Customer Perspective,Internal Business Process Perspective and Learning and Growth Perspective.